2004
DOI: 10.1094/phyto.2004.94.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Sclerotinia Disease on Lettuce: Toward Developing a Prediction Model for Carpogenic Germination of Sclerotia

Abstract: The feasibility of developing a forecasting system for carpogenic germination of Sclerotinia sclerotiorum sclerotia was investigated in the laboratory by determining key relationships among temperature, soil water potential, and carpogenic germination for sclerotia of two S. sclerotiorum isolates. Germination of multiple burials of sclerotia to produce apothecia also was assessed in the field with concurrent recording of environmental data to examine patterns of germination under different fluctuating conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 30 publications
2
84
0
4
Order By: Relevance
“…Abdullah et al, (2008) found that sclerotia did not grow after 7 days at 30 and 35 o C, however, when these sclerotia were incubated at 25 o C, normal myceliogenic growth resumed. Sclerotia that were exposed to 40 and 45 o C failed to grow after 21 days at 25 o C. The upper thresholds temperature for conditioning and germination of sclerotia were 20 and 25°C, respectively (Clarkson et al, 2007). The sclerotial germination of S. sclerotiorum tended to decrease as soil temperature increased from 15 to 40°C, with no germination observed at 40°C after 1 and 2 weeks, respectively (Matheron and Porchas, 2005).…”
Section: Effect Of Different Temperature Regimes On Viability Of Sclementioning
confidence: 99%
“…Abdullah et al, (2008) found that sclerotia did not grow after 7 days at 30 and 35 o C, however, when these sclerotia were incubated at 25 o C, normal myceliogenic growth resumed. Sclerotia that were exposed to 40 and 45 o C failed to grow after 21 days at 25 o C. The upper thresholds temperature for conditioning and germination of sclerotia were 20 and 25°C, respectively (Clarkson et al, 2007). The sclerotial germination of S. sclerotiorum tended to decrease as soil temperature increased from 15 to 40°C, with no germination observed at 40°C after 1 and 2 weeks, respectively (Matheron and Porchas, 2005).…”
Section: Effect Of Different Temperature Regimes On Viability Of Sclementioning
confidence: 99%
“…No apothecia formation was observed below 70 to 80% saturation. Clarkson et al (2004) showed that carpogenic germination of sclerotia occurred between 5 and 25 o C, but only when the soil water potential was >-100kPa. Above 26°C no apothecia were produced.…”
Section: Pathogen Biologymentioning
confidence: 99%
“…Above 26°C no apothecia were produced. In formed apothecia, the maturation of asci takes about 72-84 h (Clarkson et al 2004). Ascospore maturation is a complex process that is influenced by multiple factors.…”
Section: Pathogen Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…2 The interaction between RH and air temperature is pivotal to the formation of apothecia, while soil temperature and moisture influence sclerotial germination responses. 1,11 Atmospheric temperatures ranging from 5 °C to 25 °C with high RH (not quantified in the literature cited) for approximately 10 days promote the development of apothecia. 2,18 When RH is at an optimum and air temperatures are ≥30 °C or ≤5 °C, increased incubation time and reduced carpogenic germination rate have been recorded, despite optimum RH.…”
Section: Carpogenic Germinationmentioning
confidence: 99%